Prevalence of Mandibular Fractures, Maxillary Prognathism and Irreversible Pulpits in a known population - Bhoosreddy, Seema; Gondhalekar, Rajashree Rajesh; Bajpai, Ranjan; Bajpai, Chandni; Rahar, Arun; verma, Anurag (Journal of Neonatal Surgery, 2025)
Background: This study was conducted to assess the Prevalence of Mandibular Fractures, Maxillary Prognathism and Irreversible Pulpits in a known population. Material and methods: This study comprised of 100 subjects who underwent oral clinical examination. The goal of the study was to assess the prevalence of mandibular fractures, maxillary prognathism and irreversible pulpitis. The study procedure had been explained to all the subjects and the patients had been asked to give consent. All the subjects agreed to sign the consent form and hence all had been involved in the trial. The demographic characteristics of the patients were recorded and the prevalence of the above-mentioned conditions had been tabulated. Statistical analysis was conducted using SPSS software. Results: In this study, there were 35 cases of mandible fracture, 16 cases of maxillary prognathism and 49 cases of irreversible pulpitis. Hence, the prevalence of mandibular fractures, maxillary prognathism and irreversible pulpitis was 35%, 16% and 49%, respectively. There were 20 males and 15 females in group 1. Group 2 comprised of 10 males and 6 females. There were 26 males and 23 females in group 3. Overall, there were 56 males and 44 females in the trial. Conclusion: The prevalence of mandibular fractures, maxillary prognathism and irreversible pulpitis was 35%, 16% and 49%, respectively.